2021
DOI: 10.1037/emo0000904
|View full text |Cite
|
Sign up to set email alerts
|

On evidence for a dozen new basic emotions: A methodological critique.

Abstract: Much theory, research, and application regarding emotion is based on a set of basic emotions. But the question remains: which emotions are in that set? One proposal is to expand the classic set of six with 12 new ones, each indicated by a facial expression purported to convey that one specific emotion universally. A series of studies offered as support for this proposal relied on presenting participants with the emotion label embedded in a story and then asking them to choose among four facial expressions or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Research suggests that the emotion words employed in experimental trials are potent enough to actively shape the emotional meaning that the participants experience in another person’s facial movements (e.g., Doyle & Lindquist, 2018; Lindquist, 2017; Lindquist et al, 2015; Gendron et al, 2012; Lindquist & Gendron, 2013; Satpute & Lindquist, 2021). When the contextual features embedded in choice-from-array are removed, giving participants more freedom in their responses, an explosion of variation is observed, in participants from the United States and other large, urban cultural settings (Barrett et al, 2019; Kollareth et al, 2021; Russell, 1994; Russell et al, 2003; and references therein) and in people from small-scale cultures from around the world. Since 2008, 11 published articles studying participants from small-scale cultures and using a variety of less-constraining methods have documented considerable variation in the psychological meanings experienced in faces posing hypothesized prototypic expressions (Gendron et al, 2018; Gendron, Hoemann, et al, 2020; and references therein).…”
Section: The Importance Of Contextmentioning
confidence: 99%
“…Research suggests that the emotion words employed in experimental trials are potent enough to actively shape the emotional meaning that the participants experience in another person’s facial movements (e.g., Doyle & Lindquist, 2018; Lindquist, 2017; Lindquist et al, 2015; Gendron et al, 2012; Lindquist & Gendron, 2013; Satpute & Lindquist, 2021). When the contextual features embedded in choice-from-array are removed, giving participants more freedom in their responses, an explosion of variation is observed, in participants from the United States and other large, urban cultural settings (Barrett et al, 2019; Kollareth et al, 2021; Russell, 1994; Russell et al, 2003; and references therein) and in people from small-scale cultures from around the world. Since 2008, 11 published articles studying participants from small-scale cultures and using a variety of less-constraining methods have documented considerable variation in the psychological meanings experienced in faces posing hypothesized prototypic expressions (Gendron et al, 2018; Gendron, Hoemann, et al, 2020; and references therein).…”
Section: The Importance Of Contextmentioning
confidence: 99%
“…For example, for pride, the stimulus was “He/she just achieved great honor for himself and his country, and he or she feels a great sense of pride.” They found that participants were able to select the predicted “pride” face from an array of four faces of the same valence. In our critique (Kollareth et al, 2021), we showed that participants select the same “pride” face as a signal for a different emotion when combined with a different situation. For example, the hypothesized “pride face” was selected for this label + situation: “Person K is confronting a problematic roommate who has been stealing many of Person K’s items.…”
Section: Research Program On Emotions With Facial Signalsmentioning
confidence: 87%
“…Kollareth et al (2021) showed the limitations of the experimental task used by Cordaro et al (2020). Our goal in the present study was not a comparison of methods.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This confound can also artificially increase recognition accuracy. Indeed, participants assigned the same emotion expression to multiple stories that mentioned different, plausible emotion labels, leading to seeming evidence that the same expression can represent multiple emotions [39]. Finally, when participants from a remote culture could freely label expressions with emotion terms, they labeled them with terms that matched the expression's valence, yet they rarely used the predicted discrete emotion terms, rendering it unclear whether they accurately perceived the specific emotions [40,but see also 41].…”
Section: Emotion and Emotion Perceptionmentioning
confidence: 99%